2008
DOI: 10.1161/strokeaha.107.511584
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima Media Thickness and Plaques Can Predict the Occurrence of Ischemic Cerebrovascular Events

Abstract: Background and Purpose-The clinical usefulness of noninvasive measurement of carotid intima media thickness and plaque visualization in the general population is still uncertain. Methods-We evaluated the age-specific incidence rates of cerebrovascular events in a cohort of 1348 subjects randomly taken from the census list of San Daniele Township and followed for a mean period of 12.7 years. The association among common carotid intima media thickness, measured at baseline, arterial risk factors, and incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 38 publications
3
83
1
2
Order By: Relevance
“…In this regard, the findings of the present report are in keeping with a previous prospective study on an Italian population in which the incidence of cerebrovascular events is higher in patients at intermediate Framingham risk, but with presence of a carotid plaque than in those at high Framingham risk without the presence of carotid plaque as an additional risk factor [7].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In this regard, the findings of the present report are in keeping with a previous prospective study on an Italian population in which the incidence of cerebrovascular events is higher in patients at intermediate Framingham risk, but with presence of a carotid plaque than in those at high Framingham risk without the presence of carotid plaque as an additional risk factor [7].…”
supporting
confidence: 92%
“…For instance, the addition of carotid intima-media thickness (cc-IMT) and plaque is found to improve the Framingham risk score in subjects at high vascular risk [7]. Addition of multiple biomarker scores to a traditional risk factor model has also been recently evaluated, and shows some promises [8].…”
mentioning
confidence: 99%
“…Carotid intima‐media thickening (CIMT) and carotid plaque (CP) are considered to be surrogate subclinical markers of early atherosclerosis, are associated with stroke risk (Georgios et al., 2006; Rundek et al., 2015), and can predict the occurrence of ischemic cerebrovascular events (Prati et al., 2008). There is a study that found that increased common carotid artery stiffness is associated with ischemic stroke (Tsivgoulis et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The c-IMT measurement has also been shown to be an independent risk factor that correlates well with the Framingham Stroke Risk Score (FSRS), which is a calculation of 10-year stroke risk (Touboul et al 2005). This study used five hundred and ten (510) Indeed, in a cohort study of 1348 randomly selected subjects followed for 12.7 years, its contribution to individual risk prediction has been shown to be limited for the general population but may be useful only in high-risk groups (Prati et al 2008). …”
Section: Ultrasound Techniquesmentioning
confidence: 99%